Natural Assets and Their Role in Rural Tourism (Northeastern Morocco) (Libya Journal of Geographical Studies, 2025)
Water resources are considered a natural heritage par excellence, as they contribute to the development of rural tourism offerings, particularly when water bodies are utilized for recreational and tourism-related activities or simply for the enjoyment of springs and flowing water landscapes. In this context, water transforms from a natural resource within the landscape into a natural attraction that draws visitors and supports rural development. Additionally, water serves as a fundamental element in supporting tourism offerings by supplying fresh water to tourist facilities, irrigating agricultural lands that ensure the availability of local products, and creating an environment attractive to visitors. The southern slopes and margins of the Beni Znassen Mountains in northeastern Morocco are characterized by a diversity of water resources. Springs offer appealing scenes for visitors through their emergence and flow, and they also provide mineral water and support traditional irrigation heritage. Dams (with a total storage of 335 million cubic meters) and an average annual rainfall of 500 mm at Tafoughalt Station contribute to creating an ecologically rich environment with recreational value for visitors. The findings of this research paper reveal the forms of tourism offerings in relation to water resources and the resulting commercial and service activities, which have had a positive impact on rural development in the southern slopes and margins of the Beni Znassen Mountains.
Keywords: Water resources; Beni Znassen Mountains; Northeastern Morocco; Natural potential; Rural tourism